(untitled) (Research, Society and Development, 2022)
Introduction: Verminosis are considered a public health problem, with high prevalence in childhood, with emphasis in the current Brazilian scenario for hookworm, ascariasis, enterobiosis, taeniasis and giardiasis. The main ways to prevent helminths are: proper hand and food hygiene, presence of basic sanitation and practice of socio-educational measures. Objectives: Expand information about preventive measures on worms and train both children and their respective families. Methodology: This is a descriptive research with a quanti-qualitative approach developed at the State School “Santa Terezinha”, in municipality of Patos de Minas-MG, in 2019. 37 students from the 3rd and 4th grade of elementary school participated. A questionnaire directed at parents was used, with questions regarding the incidence of worms in their children, the treatment used and routine prophylactic habits for data collection. Results and Discussion: Through the questionnaire it was noticed that the population of the observed area is vulnerable to the involvement of the worms addressed, as they do not understand the importance of prophylactic measures. Thus, the need for an expository class on the main verminosis and a quiz game addressing them was evidenced so that children are informed about it. Conclusions: In health practice, individuals should be informed about verminosis, emphasizing: necessary prophylactic measures, signs and symptoms, reducing their prevalence and facilitating their detection. Thus, it prevents the consequences to install in those affected, contributing to an improvement in the health of the population.